A STUDY ON TRADITIONAL MARKET MANAGEMENT TOWARDS BLIMBING MARKET IN MALANG CITY - Rachmad Yusuf Susanto (Unitri Press, 2017)
As related to the rate of business scale fast growth and the very tight competition in the business world, the needs of society also increase by degrees from time to time. The existence of traditional market in Indonesia is dealing with tight competition from modern market, on which the rate of modern market growth is out of control. The position of traditional market has been eliminated by slowly due to the conducive situation within modern market by which the price of goods including service offered to consumers is very competitive. That’s the fact that most of consumer prefer to go shopping to modern market instead of traditional market. Traditional market throughout Indonesia continue to make an effort to survive against the more and more aggression carried out by modern market in offering all of the goods to be selled. The government has full responsibility to protect the existence of traditional market which is a backbone of government economy especially in establishing the full employment and contributing to local government income. The analysis in this research is traditional market merchant who has established their business in Pasar Blimbing Kota Malang. This research involved the 50 respondents which were sampled by simple random sampling method, among others: direct observation, interview, scrutinize documentation, distributing questionnaires to collect primary data. While secondary data was collected indirectly from the other parties. The aim of this research is to find out more how far the active role of the government in protecting the existence of traditional market against the more and more aggression carried out by modern market in offering all of the goods to be selled.